PENINGKATAN PEREKONOMIAN UMKM MELALUI PENGEMBANGAN SISTEM INFORMASI WISATA PANTAI PENGKOLAN DI DESA KANDANGSEMANGKON - Siti Mujilahwati; Miftahus Sholihin; M.Rosidi Zamroni; Muhammad Nur Fikri Alfarisi; Muhammad Alvin Firdaus; Qonit Zirby; Muhammad Rayendra AlMuhibbi; Moh Adam Mufrody; Febrian Abie Prsatama; M Chabib Nurroziqin; Achmad Nurasel Farizki (Program Vokasi Universitas Negeri Gorontalo, 2024)
Kandangsemangkon Village, situated on the northern coast of Lamongan Regency, exhibits considerable potential for tourism development, largely due to its proximity to the notable Pengkolan Beach. However, the absence of effective promotional strategies and a lack of visibility represent a significant challenge in the development of tourism and the empowerment of local micro, small, and medium-sized enterprises (MSMEs). The objective of this community service program is to enhance the visibility of Pengkolan Beach and bolster the local economy through the establishment of a comprehensive tourism information system website. A series of activities, including field surveys, website development, training for MSMEs, and digital promotion, has enabled the creation of an effective platform for introducing the tourism potential and local products of the area to a wider audience. While there is no specific measurement regarding visibility, the positive response from the community and MSME actors indicates that this website has had a significant impact. The results of this program demonstrate an increase in the promotion of tourist destinations and sales of MSME products. To ensure the sustainability of this program, it is essential to prioritize website maintenance, continued training, and the enhancement of tourism infrastructure. Consequently, Kandangsemangkon Village can continue to develop as a renowned tourist destination, which will ultimately reinforce the local economy and community welfare.